PENGARUH UKURAN PERUSAHAAN, KINERJA KEUANGAN, OPINI AUDIT DAN ROTASI AUDITOR TERHADAP AUDIT DELAY - Mesir, Khairul (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
The aim of this research is to determine and analyze the influence of company size, financial performance as measured by profitability ratios and solvency ratios, audit opinions and auditor rotation on audit delay. The population used in this research is various industrial subsector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. This type of research is quantitative research with secondary data. Determining the data sample in this research uses a purposive sampling technique, namely by determining predetermined criteria. The sample of companies used in this research was 45 people and the method used was a panel data regression model with analysis tools using Eviews version 12. The results of research on companies in various subsectors of industry show that the variables of company size, profitability, solvency, audit opinion and audit rotation are consistent. simultaneously has a significant effect on audit delay and partially the variables of company size, profitability and solvency have a negative effect on audit delay, while the audit opinion and audit rotation variables have no effect on audit delay.